ЕВОЛЮЦІЯ ТА ПОШИРЕННЯ СПЕЦІАЛІЗОВАНИХ СТРАТЕГІЙ, МЕТОДІВ І ТЕХНІК СИНХРОННОЇ ШИРОТНО-ІМПУЛЬСНОЇ МОДУЛЯЦІЇ ДЛЯ КЕРУВАННЯ ІНВЕРТОРАМИ ДЖЕРЕЛ НАПРУГИ ТА СИСТЕМАМИ НА ОСНОВІ ІНВЕРТОРІВ - Олещук, В. (Інститут електродинаміки НАН України, Київ, 2023)
This publication provides a brief historical overview of the development of methods and techniques of pulsewidth modulation (PWM) for voltage source inverters, published mainly in Ukrainian publishing houses and in Ukrainian periodicals. Accent has been done to review of results of investigation of alternative methods and techniques of synchronous space-vector-based multi-zone PWM for inverters with low switching frequency. In particular, in the mentioned publications, the basic strategies, schemes, and algorithms of synchronous multi-zone modulation have been further developed, modernized, modified, and disseminated in relation to new promising topologies of power conversion systems, including: two-inverter-based electric drives with open-end winding of electrical motor; dual three-phase electric drives of symmetrical and asymmetric types; powerful six-phase systems based on four inverters, and two-inverter-based and three-inverter-based photovoltaic installations with multi-winding transformer. It is shown that the developed schemes and algorithms of synchronous space-vector PWM, applied for control of inverter-based systems, provide continuous synchronization and symmetry of basic voltage waveforms of systems during the whole control range including zone of overmodulation of inverters. It provides minimization of even harmonics and undesirable subharmonics (of the fundamental frequency) in spectra of the basic voltages of systems, leading to reducing of losses in systems and to increasing of its efficiency. Based on a comparative analysis of the integral spectral characteristics of the phase and line voltages of systems, recommendations are formulated for the rational choice of schemes and algorithms of synchronous modulation for the relevant installations, depending on the modes of their operation. References 30, tables 2, figures 25.